2014
DOI: 10.5539/gjhs.v7n1p98
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Trastuzumab in the Adjuvant Treatment for Early Breast Cancer

Abstract: Background:Evidence from randomized controlled trials (RCTs) has shown a significant survival advantage of trastuzumab. Although extant work in developed countries examined economic evaluation of trastuzumab in adjuvant treatment for early breast cancer based on the 1-year treatment, there is uncertainty about cost-effectiveness of trastuzumab in the Adjuvant Treatment of early breast cancer in developing countries. This study aimed to estimate cost-effectiveness of adjuvant trastuzumab therapy compared to AC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 31 publications
4
43
1
1
Order By: Relevance
“…14 Similarly, a cost-effectiveness analysis performed in Iran of 1-year trastuzumab adjuvant chemotherapy for early breast cancer, estimating outcomes, coverage and costs over a 20-year period, concluded that the treatment would not be cost-effective in this country. 15 The same conclusion was reached in a pharmacoeconomic study evaluating the addition of trastuzumab to standard chemotherapy in patients with advanced gastric cancer in China. 16 On the other hand, 1-year trastuzumab adjuvant chemotherapy for early breast cancer has been found cost-effective in Taiwan where, since 2010, the national health system (NHS) started to reimburse the treatment, having fixed a willingnessto-pay threshold at 3-times the per capita gross domestic product.…”
Section: Anti-erbb2 Approved Productsmentioning
confidence: 61%
“…14 Similarly, a cost-effectiveness analysis performed in Iran of 1-year trastuzumab adjuvant chemotherapy for early breast cancer, estimating outcomes, coverage and costs over a 20-year period, concluded that the treatment would not be cost-effective in this country. 15 The same conclusion was reached in a pharmacoeconomic study evaluating the addition of trastuzumab to standard chemotherapy in patients with advanced gastric cancer in China. 16 On the other hand, 1-year trastuzumab adjuvant chemotherapy for early breast cancer has been found cost-effective in Taiwan where, since 2010, the national health system (NHS) started to reimburse the treatment, having fixed a willingnessto-pay threshold at 3-times the per capita gross domestic product.…”
Section: Anti-erbb2 Approved Productsmentioning
confidence: 61%
“…Modelling, however, often involves the use of many assumptions often based on adjustments of findings from earlier studies [40,47,55,59,60]. The reasonableness of these assumptions, however are central to the quality of model and the validity of its predictions.…”
Section: Modellingmentioning
confidence: 99%
“…For example, different studies use different modelling approaches, while most use a Markov modelling approach (including health-state transition model [47,61,62], life-long state transition model [63], a discrete-state time dependent semi-Markov model [64]), others use dynamic models (dynamic life-cycle model [35]). The number of states modelled also varies markedly from 3 to 10 states of disease [45,47,51,55,59,64], the variation reflecting in part the focus of the authors (such as cardiac toxicity, recurrence or relapse, HER2 testing and Trastuzumab regime) and the willingness of authors to balance complexity with transparency in models. How models are populated also varies though the relatively small number of trials relating to use of Trastuzumab in early stage breast cancer has served to limit heterogeneity here.…”
Section: Modellingmentioning
confidence: 99%
“…Breast cancer as the most common cancer among Iranian females (Aboutorabi, Hadian, Ghaderi, Salehi, & Ghiasipour, 2015), is word widely the 18% proportional share of all cancers in women (Cvetković & Nenadović, 2016). Certainly, the prerequisites for the disease prevention and proficient treatment findings are the precise detection of affective risk factors in diseases formation and progression (Mert, Kılıç, Bilgili, & Akan, 2015).…”
Section: Introductionmentioning
confidence: 99%